A review of Data Infrastructure for Education: A Proposal for Improved Decision Making in XYZ University - Lê Thắng Thục (Jejaring Penelitian dan Pengabdian Masyarakat, 2025)
Data is becoming a valuable resource for organisations in a variety of industries today, including education. Educational institutions are constantly gathering massive volumes of data from many sources. XYZ University (XYZU), one of the higher educational institutions, has issues with its current data infrastructure, which slows down its decision-making. The existing system relies on reporting and analytics that are derived directly from operational applications, which leads to data silos and discrepancies. To address these issues, this paper proposes a data architecture that combines data from several source applications to facilitate integrated reporting. The paper explores the background and problems in terms of data storage, management, and use of enterprise data, followed by a problem statement, a discussion of data integration, and a proposed technical architecture.